2016
DOI: 10.1038/srep30275
|View full text |Cite
|
Sign up to set email alerts
|

Multibody cofactor and substrate molecular recognition in the myo-inositol monophosphatase enzyme

Abstract: Molecular recognition is rarely a two-body protein-ligand problem, as it often involves the dynamic interplay of multiple molecules that together control the binding process. Myo-inositol monophosphatase (IMPase), a drug target for bipolar disorder, depends on 3 Mg2+ ions as cofactor for its catalytic activity. Although the crystallographic pose of the pre-catalytic complex is well characterized, the binding process by which substrate, cofactor and protein cooperate is essentially unknown. Here, we have charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…However, an empirical rule has been known in the community of specialists applying MSMs to study biomolecules, namely, that the slowest implicit timescale captured by an MSM can go up to the values on the same order of magnitude as the aggregate sampling achieved in the used MD dataset. In previous studies of specific biomolecular systems with MSMs based on MD simulations, reported longest implicit timescales turned out to be smaller than the aggregate sampling by at least one order of magnitude [5][6][7][8][9][10][11][12][13][14][15][16][17] or comparable to the aggregate sampling. [18][19][20][21][22] In this paper, we analyze several MSMs with different topologies to uncover the reasons for the above empirical rule.…”
Section: Introductionmentioning
confidence: 99%
“…However, an empirical rule has been known in the community of specialists applying MSMs to study biomolecules, namely, that the slowest implicit timescale captured by an MSM can go up to the values on the same order of magnitude as the aggregate sampling achieved in the used MD dataset. In previous studies of specific biomolecular systems with MSMs based on MD simulations, reported longest implicit timescales turned out to be smaller than the aggregate sampling by at least one order of magnitude [5][6][7][8][9][10][11][12][13][14][15][16][17] or comparable to the aggregate sampling. [18][19][20][21][22] In this paper, we analyze several MSMs with different topologies to uncover the reasons for the above empirical rule.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium chloride is used to diminish behavioural symptoms of these diseases, such as the manic phase symptoms observed in bipolar patients [46], which include sleeplessness, hallucinations, psychosis, or paranoid rage [47]. One of the most accepted mechanisms of lithium action is the inositol depletion hypothesis [44] which suggest that lithium acts by blocking the IMPase 1 enzyme activity, leading to a depletion of inositol in the brain of treated patients [44,45,48,49]. Therefore, we predicted that we could rescue normal behaviour in infected stickleback by modulating the inositol pathway using lithium exposure.…”
Section: Functional Analysis In Infected Sticklebacks: Pharmacologicamentioning
confidence: 99%
“…Therefore, we predicted that we could rescue normal behaviour in infected stickleback by modulating the inositol pathway using lithium exposure. We measured two wellcharacterized behaviours in infected individuals: [48], which is implicated in a diverse range of responses in the central nervous system [44,54].…”
Section: Functional Analysis In Infected Sticklebacks: Pharmacologicamentioning
confidence: 99%
“…In a recent work, Ferruz et al, a complex multi-cofactor and substrate binding to myo-inositol monophosphatase (IMPase) and its underlying dynamic interplay was studied by means of all-atom MD simulations and using MSM and adaptive sampling scheme [45]. IMPase is an enzyme that depends on 3 Mg 2+ ions as cofactors for its catalytic activitytheir binding poses are known but the way cofactors and substrate cooperate is unknown.…”
Section: Multibody Binding Studiesmentioning
confidence: 99%
“…While crystallography-derived structures provide essentially static conformations, and magnetic resonance (NMR) experiment provide a limited range of dynamic information, the conformational space sampled by MD is largely determined by the computing resources available. Pioneering studies have indeed been able to capture full and repeated folding and unfolding of domains, albeit on selected fast-folding targets [45,46]. Extended sampling is especially important for targets undergoing large conformational changes during their activity.…”
Section: Conformational Rearrangements and Unstructured Proteinsmentioning
confidence: 99%